Contestation of European Economic Migration after 2004 in France : Case Study of the ‘Polish Plumber’ - Menu, Sabine; Błażejczyk-Majka, Lucyna (Sensus Historiae, 2025)
Economic migration is a cornerstone of the Single European Market, which is founded on the principle of unfettered freedom of movement. But when the EU underwent its biggest enlargement, the expression ‘Polish plumber’ emerged in France from 2004 onwards to denounce the pressure on the labour market generated by what was deemed unfair social competition from the new Member States. The study compares the political uses of this expression in France with demographic statistics, and highlights that its main impact can be likened to a non-tariff barrier regularly claimed to limit the free movement of people.